(untitled) (Tikrit Journal For Political Science, 2024)
The roots of the contemporary Ukrainian issue date back to 1991 with the dissolution of the Soviet Union, and Ukraine’s independence in the same year. In 1994, the "Budapest Memorandum" was signed, in which the Russian Federation pledged to respect Ukraine’s borders in exchange for Kyiv’s abandonment of its nuclear arsenal inherited from the Soviet Union in favor of Russia. However, geopolitical calculations quickly asserted themselves in Eastern Europe, with NATO’s eastward expansion. The Czech Republic, Hungary, and Poland joined the alliance in 1999, and between 2004 and 2009, nine Eastern European countries, some from former Soviet republics (Bulgaria, Estonia, Latvia, Lithuania, Romania, Slovakia, Slovenia, Albania, Croatia), followed suit. Later, Montenegro and North Macedonia joined, making a total of around 14 countries that joined the alliance between 1999 and 2020, constituting about half of the NATO member states founded in 1949.